THE APPLICATION OF ABDOMINAL STRETCHING EXERCISES ON REDUCING MENSTRUAL PAIN INTENSITY IN ADOLESCENTS - Rina Karmila (Getsempena Health Science Journal, 2024)
Dysmenorrhea is one of the reproductive health problems that some young women always experience during menstruation. One non-pharmacological therapy that is safe to reduce dysmenorrhea pain is abdominal stretching exercises. This research aims to describe the application of abdominal stretching exercise therapy to reduce the intensity of menstrual pain in young women at the IM Banda Aceh Kesdam Nursing Academy. The design of this research is descriptive research using a case study approach method. This data collection technique was through interviews with five teenagers with dysmenorrhea with the criteria of teenagers with menstrual pain, mild and moderate pain, and no fractures. The results of the study showed that menstrual pain before the intervention was carried out on a scale of 5 on subject I, on subject II on a scale of 6, on subject III on a scale of 3, on subject IV on a scale of 5, and on subject V on a scale of 4. Menstrual pain after the intervention on subject I scale 3, in subject II scale 4, in subject III scale 1, in subject IV scale 3, and in subject V. This research proves that the application of abdominal stretching exercises to young women who experience dysmenorrhea can reduce the intensity of menstrual pain. It is hoped that abdominal stretching therapy can be applied as an alternative action to reduce the intensity of menstrual pain in teenagers.